A Comparative Research on Municipal Voluntary Tasks of Three Hungarian and Slovenian Municipalities - Marianna Nagy; István Hoffman; Dorottya Papp (Central European Public Administration Review)
The article summarizes the similarities and differences in voluntary task management of municipalities. For this purpose, we carried out empirical research in three Hungarian and three Slovenian municipalities. Our main objective was to discover which economic and social factors influence the scope of voluntary tasks in Hungary and in Slovenia. We separately analysed six sectors of municipal services, with regard to the different size of the municipalities. Likewise, we only covered the major sectors in which voluntary tasks are most likely to appear and therefore can serve as a basis for comparative analysis. The analysis gradually verified the initial hypothesis of our research that voluntary tasks management is more likely to be present in cities with larger economic powers and is remarkably profounder in municipalities of touristic importance.